2008
DOI: 10.1080/07420520802572333
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte Subset Redistribution in a Human Model of Physical Stress

Abstract: This study has investigated, under controlled conditions, peripheral mononuclear cells (PMNC) subset redistribution in a human experimental stress model consisting of cycloergometer activity in healthy male volunteers exposed to a stressful stimulus. After stressful stimuli, leucocyte subpopulations undergo a stereotyped redistribution peculiar for each PMNC cytotype. PMNC subpopulations involved to a greater extent were natural killer (NK) cells and lymphocytes T "memory" cells. The post-stress period was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Exclusion criteria were acute (at the moment of the investigation) or chronic infections, allergy, acute (at the moment of the investigation) or chronic use of medicines, tobacco use, known hypersensitivity, or allergy to pharmacological agents including non-steroid anti-inflammatory drugs (NSADs). Before being admitted to the exercise phase of the investigation, volunteers' maximum oxygen consumption (VO 2 max ) was assessed as detailed in a previous study of our group (18).…”
Section: Subjectsmentioning
confidence: 99%
“…Exclusion criteria were acute (at the moment of the investigation) or chronic infections, allergy, acute (at the moment of the investigation) or chronic use of medicines, tobacco use, known hypersensitivity, or allergy to pharmacological agents including non-steroid anti-inflammatory drugs (NSADs). Before being admitted to the exercise phase of the investigation, volunteers' maximum oxygen consumption (VO 2 max ) was assessed as detailed in a previous study of our group (18).…”
Section: Subjectsmentioning
confidence: 99%
“…Recent evidence has also shown that decidual NK (dNK) cells play a key role in controlling trophoblast invasion and vascular remodeling (33,34). Although NK cells are an important cell type within the innate immune system and also act as sentinel cells in other models (35)(36)(37), their exact function at the maternal-fetal interface remains incompletely defined. Recent studies have reported that CD27, which belongs to the TNF receptor family, is an important marker in distinguishing different subsets of NK cells (38,39).…”
mentioning
confidence: 99%
“…Significant physical exercise usually results in pronounced changes in blood cell composition: it increases the number of circulating mononuclear cells (lymphocytes, monocytes), and granulocytes and changes the ratio of lymphocytic subpopulations (Mignini et al 2008;Timmons et al 2008). Specific cell types such as NK-and T cells are known to be preferentially mobilized in the blood after acute exercise (Gleeson et al 2006;Maltseva et al 2011;Mooren et al 2002).…”
Section: Mt Datamentioning
confidence: 98%